Porous cellulose particles and method for producing same

Porous cellulose particles with controlled sizes and surface openings are produced using alkali hydroxide and urea solvents, addressing the limitations of existing methods by enhancing suitability for chromatography and reducing environmental impact.

JP7618557B2Active Publication Date: 2025-01-21DAICEL CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2021537265
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-08-02
Filing Date
2020-07-30
Publication Date
2025-01-21
Estimated Expiration
2040-07-30

AI Technical Summary

Technical Problem

Existing methods for producing cellulose particles with chitosan result in large particle sizes and lack of surface pores, making them unsuitable for fast mass transfer processes like chromatography, especially for high molecular weight samples, and involve harmful chemicals that affect the micro to macro structure.

Method used

The production of porous cellulose particles using alkali hydroxide and urea as solvents, dissolving chitosan in a small amount of acid and cooling it, followed by mixing with cellulose to create particles with predetermined openings and sizes, and incorporating an acid washing step to suppress chitosan elution.

Benefits of technology

The method produces cellulose particles with surface pores and controlled sizes, suitable for chromatography, acting as anion exchangers and adsorbents, while minimizing chitosan elution and environmental impact.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007618557000001
    Figure 0007618557000001
  • Figure 0007618557000002
    Figure 0007618557000002
  • Figure 0007618557000003
    Figure 0007618557000003
Patent Text Reader

Abstract

Provided are porous cellulose particles that have prescribed openings on the surface thereof and a prescribed particle size, and contain chitosan. Also provided is a production method for said particles. The porous cellulose particles contain chitosan and unsubstituted cellulose and in said particles: the chitosan content is no more than 20 mass% of the total 100 mass% of the unsubstituted cellulose and the chitosan; pores that are 0.05-5 μm in diameter are observed in an image obtained by observing the surfaces of the porous cellulose particles using a scanning electron microscope; and the ratio of porous cellulose particles with a particle size of 10-200 μm is at least 90 mass%.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to porous cellulose particles and methods for producing the same. [Background technology]

[0002] Polysaccharides, such as cellulose, and their derivatives are used in a variety of applications. For example, these microporous materials can themselves act as adsorbents, and their surfaces can be chemically modified to provide them with functions such as adsorption, separation, and catalysis.

[0003] For example, various methods for producing matrices for biopolymer separation using cellulose, agarose, etc. have been disclosed, and their usefulness is well known. In order to give functionality to the surface of cellulose and other polysaccharides, chemical modification is performed. For example, when the -OH group of a sugar is reacted with chloroacetic acid under basic conditions, carboxymethyl ether is produced, and when it is reacted with 1-chloro-2-(diethylamino)ethane, diethylaminoethyl ether is produced, and each of these is used as a weak ion exchanger. However, such chemical modification not only increases the production cost, but also requires the use of harmful chemicals and may have a negative effect on the micro- to macro-structure of the particles. For this reason, a simpler method for introducing functional groups is desired.

[0004] One possible way to solve these problems is to blend a polymer that has a function that cellulose does not originally have. In this sense, if chitosan, which has anion exchange ability and contains amino groups that can serve as a scaffold for binding various atomic groups, can be blended, it is expected that various functions can be imparted to cellulose beads. Since cellulose and chitosan do not necessarily have a common solvent, there have been attempts to mix one powder with the solution of the other and mold it (see Patent Documents 1 and 2). However, since the molded product obtained in this way retains the properties of cellulose and chitosan, chitosan will dissolve if washed with an acidic aqueous solution, for example.

[0005] For example, Patent Document 3 discloses that a certain amount of spray-dried chitosan is first dissolved in N-methylmorpholine N-oxide (NMMO), then cellulose is added to obtain a solution with a chitosan to cellulose composition ratio of 0 / 100 to 5 / 95, and the solution is dropped as droplets from a syringe into water to solidify. However, the beads have a diameter of 2 to 3 mm, and SEM observation of a freeze-dried sample shows that no pores are formed on the surface. The particle size of the beads described in Patent Document 3 and the lack of pores on the surface make them unsuitable for processes requiring high mass transfer speed, such as chromatography, and in particular cannot be used practically in chromatography processes that handle high molecular weight samples such as proteins and nucleic acids. [Prior art documents] [Non-patent literature]

[0006] [Non-Patent Document 1] Carbohydrate Polymers, 150 (2016), Pages 216-226 [Non-Patent Document 2] Cellulose (2014) 21:4405-4418 [Non-Patent Document 3] Carbohydrate Polymers, 54,(4)2003, 425-43 Summary of the Invention [Problem to be solved by the invention]

[0007] A primary object of the present disclosure is to provide chitosan-containing porous cellulose particles having predetermined open pores on the surface and a predetermined particle size, and a method for producing the same. [Means for solving the problem]

[0008] In contrast to the above-mentioned conventional techniques, the inventors of the present disclosure have focused on the use of an aqueous solution containing an alkali hydroxide and urea as a solvent that is inexpensive, safe, and has a small environmental impact, such as odor, in the development of porous cellulose particles containing chitosan. However, chitosan, which is a basic polymer, dissolves well in acids but generally does not dissolve easily in alkaline aqueous solutions. In fact, even if commercially available chitosan is added to an aqueous solution of an alkali hydroxide and urea, it does not dissolve at all.

[0009] Therefore, the inventors of the present disclosure have succeeded in dissolving chitosan by first dissolving it in a small amount of acid, then adding excess alkali hydroxide and urea, and cooling it to dissolve it. By mixing this with a cellulose solution in the same solvent, they have succeeded in obtaining porous cellulose particles that contain chitosan despite being porous cellulose particles, and surprisingly, in which the chitosan is prevented from eluting even when immersed in an acid aqueous solution. In an environment with an appropriate pH, such porous cellulose particles can become an anion exchanger, an adsorbent for metal ions, and can also serve as a carrier for chromatography. In addition, various functions can be imparted to chitosan by modifying the amino groups of chitosan.

[0010] The present disclosure was completed based on these findings and through further investigation.

[0011] Item 1. Porous cellulose particles containing unsubstituted cellulose and chitosan, the content of the chitosan is 20% by mass or less in a total of 100% by mass of the unsubstituted cellulose and the chitosan, In an image of the surface of the porous cellulose particles observed with a scanning electron microscope, pores having a diameter of 0.05 to 5 μm are observed, Porous cellulose particles, in which the proportion of porous cellulose particles having a particle diameter of 10 to 200 μm is 90 mass % or more. Item 2. The porous cellulose particles according to item 1, wherein the solid content of the porous cellulose particles in a water-containing state, as measured by the following method, is 10 mass % or less. (Method for measuring solid content) The porous cellulose particles in the state of settling in the pure water are left to stand for one day or more in an environment at atmospheric pressure and at a temperature of 25°C. Next, about 2 mL of the porous cellulose particles in the pure water are sucked up with a pipette, dispersed in 20 mL of a solution in which a neutral detergent is diluted 1000 times with pure water, and left to stand for one day or more to allow the porous cellulose particles to settle. Thereafter, the supernatant is removed by decantation, and about 1 / 3 of the remaining slurry is dropped onto a filter paper equivalent to the three types specified in JIS P 3801 [filter paper (for chemical analysis)] as one sample, and left for 20 seconds to remove excess moisture, and then the mass of the porous cellulose particles remaining on the filter paper is peeled off from the filter paper and weighed to obtain the wet mass of the porous cellulose particles. Next, the porous cellulose particles are dried in an oven at 80°C for two hours and then weighed to obtain the dry mass. These operations are performed on three samples, and the ratio of the dry mass to the wet mass is calculated for each sample, and the average of the three values ​​obtained is obtained as the solid content. Item 3. A mixed solution preparation step of preparing a mixed solution by mixing an unsubstituted cellulose solution and a chitosan solution; contacting the mixed solution with a coagulation solvent; It is equipped with A method for producing porous cellulose particles, wherein an aqueous solution containing an alkali hydroxide and urea is used as a solvent for the mixed solution. Item 4. The method for producing porous cellulose particles according to Item 3, further comprising an acid washing step of washing with an acid the porous cellulose particles obtained in the step of contacting the mixed solution with a coagulation solvent. Item 5. The method for producing porous cellulose particles according to Item 4, wherein in the porous cellulose particles after the acid washing step, the chitosan content is 1% by mass or more and 20% by mass or less, based on a total of 100% by mass of the unsubstituted cellulose and the chitosan. Item 6. The method for producing porous cellulose particles according to any one of Items 3 to 5, wherein the mixed solution preparation step includes the following steps: A step of dissolving chitosan in an acid-containing aqueous solution, and further mixing an alkali hydroxide and urea to obtain the chitosan solution. A step of mixing unsubstituted cellulose, an alkali hydroxide, urea, and water to obtain a solution of the unsubstituted cellulose. mixing the chitosan solution, which has been cooled to a temperature of -10°C or lower, with the unsubstituted cellulose solution; Effect of the Invention

[0012] According to the present disclosure, it is possible to provide chitosan-containing porous cellulose particles having a specified opening on the surface and a specified particle size, and a method for producing the same. [Brief description of the drawings]

[0013] [Figure 1] 1 is an image of the porous cellulose particles obtained in Example 1 observed with an optical microscope. [Diagram 2] 1 is an image of the porous cellulose particles obtained in Example 1, observed with a scanning electron microscope. [Diagram 3] 2 is an image of the porous cellulose particles obtained in Example 2 observed with an optical microscope. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The porous cellulose particles of the present disclosure are porous cellulose particles containing unsubstituted cellulose and chitosan, characterized in that the chitosan content is 20% by mass or less in a total of 100% by mass of unsubstituted cellulose and chitosan, and in an image of the surface of the porous cellulose particles observed with a scanning electron microscope, pores having a diameter of 0.05 to 5 μm are observed, and the proportion of porous cellulose particles having a particle size of 10 to 200 μm is 90% by mass or more. The porous cellulose particles of the present disclosure are porous cellulose particles containing chitosan, having predetermined openings on the surface and a predetermined particle size.

[0015] Furthermore, the porous cellulose particles of the present disclosure that exhibit such functionality can be suitably produced by adopting a method for producing porous cellulose particles, as described below, that includes, for example, a mixed solution preparation step of preparing a mixed solution by mixing an unsubstituted cellulose solution with a chitosan solution, and that uses an aqueous solution containing an alkali hydroxide and urea as the solvent for the mixed solution.

[0016] The porous cellulose particles and the method for producing the same according to the present disclosure will be described in detail below.

[0017] 1.Porous cellulose particles The porous cellulose particles of the present disclosure contain unsubstituted cellulose (hereinafter sometimes simply referred to as "unsubstituted cellulose") and chitosan.

[0018] In the present disclosure, unsubstituted cellulose means that the hydroxyl groups of cellulose are not substantially substituted (i.e., it is not substituted cellulose), and is, for example, cellulose with a degree of substitution of hydroxyl groups of 0.05 or less. The degree of polymerization of unsubstituted cellulose is not particularly limited, but is preferably, for example, 1000 or less. If the degree of polymerization is 1000 or less, the dispersibility and swelling property in an alkaline aqueous solution described later will be high, which is preferable. In addition, if the degree of polymerization of unsubstituted cellulose is 10 or more, the mechanical strength of the obtained porous cellulose particles will be high, which is preferable. The preferable range of the degree of polymerization of unsubstituted cellulose is about 10 to 1000.

[0019] In the present disclosure, chitosan is a β-1,4-dehydration condensation polymer of glucosamine. Industrially, chitosan is obtained by extracting chitin, which is a component of crab shells, and further hydrolyzing the acetyl groups by alkaline hydrolysis. However, chitosan that is usually sold has more or less unreacted acetyl groups remaining, and generally, chitosan in which 60% or more of the acetylamino groups are converted to amino groups is called chitosan. There is a range of acetyl group content and polymerization degree, but in the present disclosure, there is no particular restriction as long as the chitosan can be mixed with porous cellulose. However, from the viewpoint of suppressing elution from porous cellulose particles, it is desirable that the number average polymerization degree of chitosan is 10 or more. The upper limit of the number average polymerization degree of chitosan is, for example, 500 or less, and a preferred range is 50 to 300.

[0020] In the porous cellulose particles of the present disclosure, the chitosan content is 20% by mass or less in a total of 100% by mass of unsubstituted cellulose and chitosan. In the present disclosure, the chitosan content is set to 20% by mass, and thus the porous cellulose particles have a predetermined pore on the surface and a predetermined particle size. The upper limit of the chitosan content is preferably 15% by mass or less, more preferably 10% by mass or less, and even more preferably 8% by mass or less, and the lower limit is preferably 1% by mass or more, more preferably 2% by mass or more, and even more preferably 3% by mass or more. Preferred ranges include about 1 to 20% by mass, about 1 to 15% by mass, about 1 to 10% by mass, about 1 to 8% by mass, about 2 to 20% by mass, about 2 to 15% by mass, about 2 to 10% by mass, about 2 to 8% by mass, about 3 to 20% by mass, about 3 to 15% by mass, about 3 to 10% by mass, and about 3 to 8% by mass. The chitosan content can be measured by washing the porous cellulose with pure water, drying it, and then performing elemental analysis using cauterization, which is a common method (the chitosan content can be converted by multiplying the nitrogen content by 161 / 14).

[0021] The porous cellulose particles of the present disclosure are porous in that pores having a diameter of 0.05 to 5 μm are observed on the surface of the particles in an image obtained by observing the particles with a scanning electron microscope. The porous cellulose particles of the present disclosure have a ratio of porous cellulose particles having a particle diameter of 10 to 200 μm of 90% by mass or more. The upper limit of the ratio is, for example, 95% by mass or less, 98% by mass or less, 99% by mass or less, 100% by mass or less, etc. Even when the porous cellulose particles of the present disclosure include porous cellulose particles having a particle diameter other than 10 to 200 μm, the particle diameter of the porous cellulose particles of the present disclosure is preferably in the range of about 1 to 600 μm.

[0022] One of the uses of the porous cellulose particles of the present disclosure is as a carrier for selective separation or reaction by binding atomic groups having some function to the surface. The form is often fine particles, and is used for filling a column for separation and purification by chromatography, or for dispersing in a liquid for selective adsorption or selective reaction. For this purpose, it is necessary that the diffusion or permeation of substances inside and between the inside and outside of the carrier particles is rapid. For this purpose, it is necessary that the particles have a predetermined particle size and have a predetermined opening. Furthermore, it is preferable that the inside of the porous cellulose particles has a structure in which the ratio of space is overwhelmingly larger than the solid (for example, a structure in which fibers are entangled). Such a structure is expressed by forming a low-density gel in which the solid content of the porous cellulose particles in a water-containing state is 10 mass% or less. That is, in this structure, the porous cellulose particles have the appearance of solid particles, but the spaces of 5 μm or less that cannot be seen with the naked eye account for approximately 90 volume% or more, and these holes or spaces are filled with liquid (water in the case of a water-containing gel). The solid content is, for example, at least 1% by mass, preferably at least 3% by mass, and preferably in the range of 1 to 10% by mass, or 3 to 10% by mass. The solid content of the porous cellulose particles in a water-containing state is measured by the following method.

[0023] (Measurement of solid content) The porous cellulose particles in the state of settling in the pure water are left to stand for one day or more (usually within three days) in an environment at atmospheric pressure and temperature of 25°C. Next, about 2 mL of the porous cellulose particles in the pure water are sucked up with a pipette, dispersed in 20 mL of a solution in which a neutral detergent (for example, Lion Corporation's product name Mama Lemon) is diluted 1000 times with pure water, and left to stand for one day or more (usually within three days) to allow the particles to settle. The supernatant is then removed by decantation, and 1 / 3 of the remaining slurry is dropped as one sample onto filter paper (for example, No. 131 150 mm manufactured by ADVANTEC Co., Ltd.) corresponding to the three types specified in JIS P 3801 [Filter paper (for chemical analysis)], and left for 20 seconds to remove excess moisture, after which the mass of porous cellulose particles remaining on the filter paper is peeled off from the filter paper and weighed to obtain the wet mass of the porous cellulose particles. Next, the porous cellulose particles are dried in an oven at 80°C for two hours to obtain the dry mass. These operations are carried out for three samples, the ratio of the dry mass to the wet mass is calculated for each sample, and the average of the three values ​​obtained is taken as the solids content.

[0024] The porous cellulose particles of the present disclosure are preferably obtained in a state dispersed or immersed in water, as described below. The porous cellulose particles of the present disclosure are in a water-containing state in water and form a water-containing gel. In addition, the porous cellulose particles of the present disclosure can be stored in a normal water-wet state.

[0025] When storing for a long period of time in a moist state, preservatives such as alcohol or sodium azide can be added to prevent spoilage. Also, the product can be dried, preferably freeze-dried, after adding glycerin, sugar, urea, etc.

[0026] In addition, the porous cellulose particles of the present disclosure exhibit functionality not found in porous cellulose composed solely of unsubstituted cellulose, and therefore can be suitably used, for example, in size exclusion chromatography. This also means that the particles can be used in various chromatographic separation modes other than size exclusion. These include ion exchange, hydrophobic, affinity, and other modes.

[0027] Furthermore, the porous cellulose particles of the present disclosure can be used as a separating agent with improved strength by covalently crosslinking cellulose or chitosan chains using a crosslinking agent.

[0028] Affinity ligands can also be immobilized on the porous cellulose particles and crosslinked porous cellulose media of the present disclosure to produce adsorbents, which can also be used as separation materials for affinity chromatography.

[0029] In the present disclosure, the method for producing porous cellulose particles is not particularly limited, so long as it is possible to obtain the porous cellulose particles of the present disclosure having the above-mentioned configuration, and the particles can be suitably produced by the production method shown in "2. Method for producing porous cellulose particles" below.

[0030] 2. Method for producing porous cellulose particles The method for producing porous cellulose particles according to the present disclosure includes a mixed solution preparation step of preparing a mixed solution by mixing an unsubstituted cellulose solution with a chitosan solution, and is characterized in that an aqueous solution containing an alkali hydroxide and urea is used as a solvent for the mixed solution. Details of the unsubstituted cellulose and chitosan are as described above in the section "1. Porous cellulose particles."

[0031] (Mixed solution preparation process) The mixed solution preparation step is a step of preparing a mixed solution by mixing an unsubstituted cellulose solution and a chitosan solution.

[0032] The unsubstituted cellulose solution is prepared using a solvent capable of dissolving unsubstituted cellulose. The chitosan solution is prepared using a solvent capable of dissolving chitosan. It is known that unsubstituted cellulose dissolves well in an alkali hydroxide aqueous solution and an alkali hydroxide-urea aqueous solution (for example, a urea-alkali hydroxide aqueous solution containing urea, thiourea, etc.). In contrast, chitosan, which has an amino group and is basic, is usually not soluble in such an aqueous solution. However, chitosan dissolves in water containing about an equal amount of acid, and a predetermined amount of alkali hydroxide and urea is added thereto, and the mixture is cooled while stirring (preferably to about -10°C to -15°C), and then the mixture is returned to room temperature and stirred continuously to obtain a chitosan solution that is somewhat thixotropic and almost uniform. By repeating this operation, the solution gradually becomes a uniform chitosan solution. Therefore, in the present disclosure, it is preferable to use an aqueous solution containing an alkali hydroxide and urea as the solvent for both the unsubstituted cellulose solution and the chitosan solution, and thus an aqueous solution containing an alkali hydroxide and urea can be used as the solvent for the mixed solution.

[0033] That is, in the method for producing porous cellulose particles of the present disclosure, the mixed solution preparation process preferably includes a step of dissolving chitosan in an acid-containing aqueous solution and further mixing with an alkali hydroxide and urea to obtain a chitosan solution, a step of mixing unsubstituted cellulose, an alkali hydroxide, urea, and water to obtain the unsubstituted cellulose solution, and a step of mixing the chitosan solution cooled to a temperature of -10°C or lower (preferably about -10°C to -15°C) with the unsubstituted cellulose solution.

[0034] A specific example of the aqueous solution containing an alkali hydroxide and urea is an aqueous solution containing 7 to 10% by mass of an alkali hydroxide and 5 to 15% by mass of urea (which may be thiourea; the same applies below). As the alkali hydroxide, lithium hydroxide and sodium hydroxide are preferred in terms of the solubility of unsubstituted cellulose and chitosan, and sodium hydroxide is preferred in terms of raw material costs. In the case of a solvent based on this aqueous alkali hydroxide solution, the solute (unsubstituted cellulose, chitosan) and the solvent are cooled to about -10°C to -15°C, preferably while stirring, and then the solution is returned to room temperature once or multiple times to form a fluid solution. Furthermore, if insoluble matter remains and adversely affects the function of the final product, the insoluble matter can be removed by filtration or centrifugation.

[0035] The term "unsubstituted cellulose solution" refers to a liquid containing unsubstituted cellulose, which shows fluidity and solidifies in a state in which unsubstituted cellulose and chitosan are compatible with each other when the unsubstituted cellulose solution is mixed with a chitosan solution and comes into contact with a coagulation solvent. It does not matter whether the unsubstituted cellulose molecules are dispersed in the unsubstituted cellulose solution, whether some associations remain, or whether fine fibrous materials are simply dispersed (sometimes called a dispersion). That is, in the method for producing porous cellulose particles of the present disclosure, the unsubstituted cellulose solution means a liquid containing unsubstituted cellulose, and is a concept that includes a dispersion in which unsubstituted cellulose is dispersed in a liquid and a solution in which unsubstituted cellulose is dissolved in a liquid. In the method for producing porous cellulose particles of the present disclosure, when preparing an unsubstituted cellulose solution, it is sufficient that the unsubstituted cellulose solution contains unsubstituted cellulose, and the form of the unsubstituted cellulose may be any of a dispersion, a dissolution, or a mixture of these.

[0036] The same is true for a chitosan solution, which refers to a liquid containing chitosan, which exhibits fluidity and solidifies in a state in which unsubstituted cellulose and chitosan are compatible with each other when the chitosan solution comes into contact with a coagulation solvent as a mixed solution mixed with an unsubstituted cellulose solution, and it does not matter whether the chitosan molecules are dispersed in the chitosan solution, whether some association remains, or whether fine fibrous materials are simply dispersed (sometimes called a dispersion). That is, in the method for producing porous cellulose particles of the present disclosure, the chitosan solution means a liquid containing chitosan, and is a concept that includes a dispersion in which chitosan is dispersed in a liquid and a solution in which chitosan is dissolved in a liquid. In the method for producing porous cellulose particles of the present disclosure, when preparing a chitosan solution, it is sufficient that the chitosan solution contains chitosan, and the form of the chitosan may be any of a dispersion, a solution, or a mixture of these.

[0037] The same applies to the mixed solution, which refers to a liquid containing unsubstituted cellulose and chitosan, which exhibits fluidity and solidifies in a state in which the unsubstituted cellulose and chitosan are compatible when the mixed solution comes into contact with a coagulation solvent, and whether the unsubstituted cellulose molecules and chitosan molecules are dispersed in the mixed solution, whether some association remains, or whether fine fibrous materials are simply dispersed (sometimes called a dispersion). That is, in the method for producing porous cellulose particles of the present disclosure, the mixed solution means a liquid containing unsubstituted cellulose and chitosan, and is a concept that includes a dispersion in which unsubstituted cellulose or chitosan is dispersed in a liquid and a solution in which unsubstituted cellulose or chitosan is dissolved in a liquid. In the method for producing porous cellulose particles of the present disclosure, the form of the unsubstituted cellulose and chitosan in the mixed solution may be either dispersed, dissolved, or a mixture thereof.

[0038] Hereinafter, the method for preparing the cellulose solution will be specifically described, taking the case where the solvent is an aqueous urea-alkali hydroxide solution as an example. A chitosan solution can also be prepared in the same manner, using chitosan as a solute. However, as for the chitosan solution, as described above, it is preferable to obtain the chitosan solution by dissolving chitosan in an aqueous acid-containing solution, and then further mixing an alkali hydroxide and urea. The acid content of the aqueous acid-containing solution may be any, such as hydrogen chloride, acetic acid, formic acid, nitric acid, or trifluoroacetic acid. In the next step, the acid is completely neutralized and an excess of an alkali hydroxide is required, so the amount of acid is preferably equal to or less than the amino group of chitosan, and is the minimum amount required to dissolve chitosan.

[0039] The alkali contained in the aqueous alkali hydroxide solution is preferably lithium hydroxide, sodium hydroxide, potassium hydroxide or quaternary ammonium hydroxide, with sodium hydroxide being most preferred from the standpoints of product safety, cost and ease of solubility or dispersion.

[0040] The alkali concentration of the aqueous alkali solution is not particularly limited, but is preferably 3 to 20% by mass excluding the portion consumed by neutralization with the acid. If the alkali concentration is within this range, the dispersibility, swelling property and solubility of the unsubstituted cellulose in the aqueous alkali solution are increased, which is preferable. The alkali concentration is more preferably 5 to 15% by mass, and even more preferably 6 to 10% by mass.

[0041] Urea is further added to the above-mentioned alkaline aqueous solution. The concentration of urea is preferably 10 to 15% by mass. The three components (cellulose, alkali hydroxide, and urea) are added to water, and the order of addition is appropriately selected to optimize the dissolution state of the cellulose. By cooling the slurry thus obtained under the conditions described later, a non-substituted cellulose solution that is more transparent than immediately after the addition of all the components is obtained.

[0042] As described above, it is preferable that the degree of polymerization of the unsubstituted cellulose is 1000 or less, since the dispersibility and swelling property in an alkaline aqueous solution are high. Another example of the unsubstituted cellulose with improved solubility is dissolving pulp.

[0043] The mixing conditions of the alkaline aqueous solution and the unsubstituted cellulose are not particularly limited as long as the unsubstituted cellulose solution can be obtained. For example, the unsubstituted cellulose can be added to the alkaline aqueous solution, or the alkaline aqueous solution can be added to the unsubstituted cellulose. When preparing a chitosan solution, the mixing conditions of the alkaline aqueous solution and the aqueous solution in which chitosan is dissolved in an acid-containing aqueous solution are not particularly limited as long as the chitosan solution can be obtained. The aqueous solution in which chitosan is dissolved in an acid-containing aqueous solution can be added to the alkaline aqueous solution, or the aqueous solution in which chitosan is dissolved in an acid-containing aqueous solution can be added to the alkaline aqueous solution.

[0044] The unsubstituted cellulose may be suspended in water before being mixed with the aqueous alkali solution.

[0045] The concentration of unsubstituted cellulose in the unsubstituted cellulose solution is not particularly limited as long as it is appropriately set to the content in the mixed solution described below, and may be, for example, about 1 to 10% by mass. The concentration of chitosan in the chitosan solution is also not particularly limited as long as it is appropriately set to the content in the mixed solution described below, and may be, for example, about 1 to 10% by mass.

[0046] The temperature at which the unsubstituted cellulose solution is prepared is not particularly limited, but for example, the unsubstituted cellulose solution is suitably prepared by mixing the unsubstituted cellulose with an alkaline aqueous solution containing urea at room temperature, cooling to a low temperature while stirring, and then returning to a temperature that is easy to handle. The temperature at which the unsubstituted cellulose solution is cooled to a low temperature is, for example, 0°C to -30°C, preferably about -5°C to -15°C. The same applies to the temperature at which the chitosan solution is prepared.

[0047] A mixed solution is prepared by mixing the unsubstituted cellulose solution and the chitosan solution. The mixing ratio of the unsubstituted cellulose solution and the chitosan solution is adjusted so as to be the content in the mixed solution described below. When the unsubstituted cellulose solution and the chitosan solution are mixed, it is preferable to thoroughly stir the unsubstituted cellulose solution and the chitosan solution so that they are mixed to form a one-phase mixed solution.

[0048] In the mixed solution, the chitosan content is preferably 20% by mass or less in the total of 100% by mass of chitosan and unsubstituted cellulose. By setting the chitosan content to 20% by mass in the mixed solution, porous cellulose particles having a predetermined particle size and a predetermined opening can be suitably obtained. From the viewpoint of more suitably exerting these properties, the chitosan content in the mixed solution is preferably 15% by mass or less, more preferably 10% by mass or less, and even more preferably 8% by mass or less, and the lower limit is preferably 1% by mass or more, more preferably 2% by mass or more, and even more preferably 3% by mass or more, and preferred ranges include about 1 to 20% by mass, about 1 to 15% by mass, about 1 to 10% by mass, about 1 to 8% by mass, about 2 to 20% by mass, about 2 to 15% by mass, about 2 to 10% by mass, about 2 to 8% by mass, about 3 to 20% by mass, about 3 to 15% by mass, about 3 to 10% by mass, and about 3 to 8% by mass.

[0049] The total concentration of chitosan and unsubstituted cellulose in the mixed solution is preferably 1 to 10% by mass. If it is 1% by mass or more, the mechanical strength of the resulting porous cellulose particles is high, which is preferable, and if it is 10% by mass or less, the viscosity of the mixed solution is low, which makes it easy to spray from a spray nozzle so as to obtain the above-mentioned predetermined particle diameter, for example. The total concentration of these in the mixed solution is more preferably 2 to 6% by mass, and even more preferably 3 to 5% by mass. Note that this total concentration in the mixed solution does not include components that are not completely dissolved, dispersed, or swollen and are not uniform.

[0050] (solidification process) In the method for producing porous cellulose particles according to the present disclosure, after the mixed solution preparation step, a coagulation step is carried out in which the mixed solution is brought into contact with a coagulation solvent, whereby the unsubstituted cellulose solution and chitosan in the mixed solution are coagulated in a compatible state to obtain porous cellulose particles.

[0051] The specific embodiment of the contact with the coagulation solvent mentioned here is not particularly limited, and known methods can be used. In the coagulation step, a typical method for obtaining porous cellulose particles is to stir and disperse the mixed solution, if necessary together with a suitable dispersant, in a liquid (such as liquid paraffin or fluorolube) that has a relatively high viscosity and is not miscible with the mixed solution, and add the coagulation solvent (a solvent that causes unsubstituted cellulose and chitosan to precipitate when mixed with the dispersion) to the obtained dispersion while stirring.

[0052] It is also possible to make the mixed solution into droplets in a gas using a spray or nozzle, and then drop these into a coagulation solvent. That is, when preparing porous cellulose particles by this method, the coagulation step can be a step of making the mixed solution into minute droplets in a gas, and then absorbing the minute droplets into a coagulation solvent. It is also possible to extrude the mixed solution into a filament, put it into a coagulation solvent, coagulate it, and then cut or crush it into amorphous particles.

[0053] The coagulation solvent is not particularly limited as long as it can precipitate unsubstituted cellulose and chitosan from the mixed solution, and examples of the coagulation solvent include organic solvents such as methanol, ethanol, and acetone, water, water in which a salt such as table salt has been dissolved, and, in the case where the mixed solution contains an alkali hydroxide, water containing an acid.

[0054] The obtained particles can be washed and used as is, but in order to prevent unnecessary components from eluting during use, it is desirable to wash the particles at least once with an acid aqueous solution. That is, the present disclosure may further include an acid washing step in which the porous cellulose particles obtained in the step of contacting the mixed solution with a coagulation solvent are washed with an acid. Even after the acid washing step, the method for producing porous cellulose particles of the present disclosure can suitably produce porous cellulose particles having a chitosan content of 1% by mass or more and 20% by mass or less. Note that even after the acid washing step, the preferred chitosan content in the porous cellulose particles is the same as that described in the column "1. Porous cellulose particles". The acid washing conditions were as follows: 3 g of porous cellulose particles, which had become a wet cake after water had been allowed to flow naturally from the top of a sieve, were washed three times with 10 mL of hydrochloric acid (0.1NHCl) (each washing took about 1 hour), once with 5 mL of water (each washing took about 1 hour), once with a solution of 0.2 g of potassium carbonate dissolved in 5 mL of water (each washing took about 1 hour), and twice with 10 mL of water (each washing took about 1 hour). It would not be surprising if all of the acid-soluble chitosan was washed out by carrying out such an operation, but in the porous cellulose particles of the present disclosure, chitosan has almost the same skeleton as cellulose and is partially incorporated into the aggregates of cellulose molecules, so that it can be said that the elution of chitosan is suppressed even when washed with an acid aqueous solution.

[0055] When storing for a long period of time in a moist state, preservatives such as alcohol or sodium azide can be added to prevent spoilage. Also, the product can be dried, preferably freeze-dried, after adding glycerin, sugar, urea, etc. EXAMPLES

[0056] The present disclosure will be described in detail below with reference to examples and comparative examples. However, each configuration and their combinations in each example are merely examples, and addition, omission, substitution, and other modifications of the configurations are possible as appropriate within the scope of the gist of the present disclosure. The present disclosure is not limited by the examples, but is limited only by the scope of the claims.

[0057] <Example 1> (Preparation of chitosan solution) 0.87g of chitosan (Chitosan 100, manufactured by Wako Pure Chemical Industries) was dispersed in 13.84g of water, to which 6.25g of hydrochloric acid (1NHCl) was added and stirred to obtain a transparent, highly viscous liquid. A solution of 2.39g of sodium hydroxide dissolved in 2.06g of water was then added little by little to this, causing a precipitate to form, making the liquid cloudy and losing fluidity. 6.42g of urea was added to this and stirred, making the liquid slightly more transparent. This liquid was cooled on dry ice until some of it crystallized into white crystals, then returned to room temperature and stirred, and this cycle was repeated three times, resulting in a liquid that was mostly transparent and thixotropic.

[0058] (Preparation of Unsubstituted Cellulose Solution) In a flask, 70.35g of sodium hydroxide was dissolved in 808.05g of water, cooled to room temperature, and 42.11g of powdered cellulose (unsubstituted cellulose Asahi Kasei Ceolas PH101) was dispersed therein while stirring. 120.05g of urea was further added and dissolved, and then cooled to -15°C for about 1 hour while stirring, and then warmed to room temperature using a water bath to become an almost transparent solution. Since the water content of the powdered cellulose was 4.25% by mass, the total solvent system was 1000.24g, unsubstituted cellulose was 40.32g, the external unsubstituted cellulose concentration was 4.0% by mass, and the internal unsubstituted cellulose concentration was 3.85% by mass.

[0059] (Preparation of mixed solution) The unsubstituted cellulose solution (90 g) and the chitosan solution (10 g) prepared above were mixed and stirred to obtain a homogeneously mixed solution.

[0060] (Atomization) The resulting mixed solution was sprayed into a mist and absorbed into methanol, yielding a fine powder in suspension. Acetic acid was added to neutralize the methanol solution, and the fine powder was filtered and repeatedly washed with water to obtain porous cellulose particles (fine particles) containing chitosan.

[0061] (acid washing) An appropriate amount of the obtained porous cellulose particles dispersed in water was placed on a 20 μm sieve, and the water was allowed to flow down by gravity. 3 g of the hydrated cake-like cellulose particles remaining on the sieve were taken and washed three times with 10 mL of hydrochloric acid (0.1NHCl) (one washing took about 1 hour), 5 mL of water, a solution of 0.2 g of potassium carbonate dissolved in 5 mL of water, and twice with 10 mL of water. The samples before and after acid washing were dried and then subjected to elemental analysis, and the N content was 0.53 mass% before acid washing and 0.52 mass% after acid washing. The N content of 0.52 mass% is equivalent to 6.0 mass% in terms of chitosan content. Since the mixture ratio of chitosan and unsubstituted cellulose in the raw solution was 7.3 mass% chitosan, about 80% of the chitosan used as the raw material was contained in the porous cellulose particles. The elemental analysis was performed using a JM10 Micro Corder manufactured by J-Science Lab Co. Ltd.

[0062] (Optical microscope observation) The obtained porous cellulose particles were washed with 50 mL of pure water containing sodium bicarbonate for 1 hour, rinsed twice with pure water, and passed through a 200 μm sieve in water to remove small amounts of lumps, and then passed through a 10 μm sieve to remove small particles smaller than this, adjusting the particle size of the porous cellulose particles to the range of 10 to 200 μm. The obtained particles were observed under water with an optical microscope using transmitted light. The product was almost spherical, and the majority of the particles were 10 to 100 μm in diameter (image in Figure 1).

[0063] (SEM observation) A small amount of the obtained porous cellulose particles was dispersed in water, dropped into a metal container cooled with liquid nitrogen, frozen, and then freeze-dried in vacuum. The obtained powder was vapor-deposited with platinum, and observed with a scanning electron microscope (HITACHI SU5000) (accelerating voltage 3 kV), revealing a porous structure with pores in the range of 0.05 to 5 μm opening on the surface. Images observed at various magnifications (250x, 1200x, 20,000x, and 100,000x) are shown in Figure 2.

[0064] (solid content) The solid content of the water-containing porous cellulose particles obtained in Example 1 was measured by the following method, and the solid content was 5.3% by mass. The porous cellulose particles in the state of settling in the pure water were left to stand for one day in an environment at atmospheric pressure and at a temperature of 25°C. Next, about 2 mL of the porous cellulose particles in the pure water were sucked up with a pipette, dispersed in 20 mL of a solution in which a neutral detergent (trade name Mama Lemon, manufactured by Lion Corporation) was diluted 1000 times with pure water, and left to stand for one day to allow the particles to settle. Thereafter, the supernatant was removed by decantation, and 1 / 3 of the remaining slurry was dropped onto a filter paper (No. 131 150 mm, manufactured by ADVANTEC Co., Ltd.) equivalent to the three types specified in JIS P 3801 [filter paper (for chemical analysis)] as one sample, and left for 20 seconds to remove excess moisture, and then the mass of the porous cellulose particles remaining on the filter paper was peeled off from the filter paper and weighed to obtain the wet mass of the porous cellulose particles. Next, the porous cellulose particles were dried in an oven at 80° C. for 2 hours to obtain the dry mass. These operations were performed for three samples, and the ratio of the dry mass to the wet mass was calculated for each sample. The average of the three values ​​obtained was taken as the solid content.

[0065] <Example 2> 9.5 parts by mass of the unsubstituted cellulose solution prepared in the same manner as in Example 1 and 0.5 parts by mass of the chitosan solution were mixed, and a portion of the mixture was added with a spoon to about 200 mL of methanol that was being vigorously stirred, causing a lumpy precipitate to form.

[0066] Next, this was stirred with a high-speed stirrer having blade-shaped rotors to obtain a slurry containing fine powder. This slurry was neutralized with a large excess of dry ice, then thoroughly washed with water, washed twice with methanol, air-dried, and vacuum-dried (80°C). Furthermore, about 1 mL of this precipitate was washed with 10 mL of hydrochloric acid (1NHCl) diluted with 55 mL of water, and 5 mL of the same diluted with 50 mL of water for 30 minutes, 5 minutes with 50 mL of pure water, and 1 hour with 50 mL of pure water containing 100 mg of sodium bicarbonate, rinsed twice with pure water, rinsed twice with 20 mL of methanol, and then air-dried and vacuum-dried (80°C). The porous cellulose particles before and after acid washing were dried from water and subjected to elemental analysis, and the nitrogen contents were 0.37% and 0.28% by mass, respectively. The nitrogen content of 0.28% in the solid content after acid washing is equivalent to 3.2% by mass in terms of chitosan content. If the entire amount of chitosan originally mixed (4.42% by mass of the total mass of cellulose and chitosan) remains, the nitrogen content is estimated to be 0.38% by mass. From this, porous cellulose particle 1 before acid washing retains almost the entire amount of chitosan, and porous cellulose particle 2 after acid washing retains approximately 74% by mass of chitosan.

[0067] (Optical microscope observation) The obtained porous cellulose particles were washed for 1 hour with 50 mL of pure water containing sodium bicarbonate, rinsed twice with pure water, and passed through a 200 μm sieve in water to remove small amounts of lumps, and then a 10 μm sieve was used to remove smaller particles, adjusting the particle size of the porous cellulose particles to the range of 10 to 200 μm. The obtained particles were observed under water with an optical microscope using transmitted light. The product was amorphous, and the majority of the particles had a major axis of approximately 30 μm. (Image in Figure 3)

[0068] (SEM observation) When the obtained porous cellulose particles were observed under a scanning electron microscope in the same manner as in Example 1, a porous structure was confirmed in which pores in the range of 0.05 to 5 μm were opened on the surface.

[0069] (solid content) When the porous cellulose particles obtained in Example 2 were impregnated with water in the same manner as in Example 1, the solid content was 4.9% by mass.

Claims

1. 1. A porous cellulose particle comprising unsubstituted cellulose and chitosan, the content of the chitosan is 1% by mass or more and 8% by mass or less in a total of 100% by mass of the unsubstituted cellulose and the chitosan, In an image of the surface of the porous cellulose particles observed with a scanning electron microscope, pores having a diameter of 0.05 to 5 μm are observed; Porous cellulose particles, in which the proportion of porous cellulose particles having a particle diameter of 10 to 200 μm is 90 mass % or more.

2. 2. The porous cellulose particles according to claim 1, wherein the solid content of the porous cellulose particles in a water-containing state, as measured by the following method, is 10% by mass or less. (Method of measuring solid content) The porous cellulose particles in the state of settling in the pure water are left to stand for one day or more in an environment at atmospheric pressure and at a temperature of 25°C. Next, about 2 mL of the porous cellulose particles in the pure water are sucked up with a pipette, dispersed in 20 ml of a solution in which a neutral detergent is diluted 1000 times with pure water, and left to stand for one day or more to allow the porous cellulose particles to settle. Then, the supernatant is removed by decantation, and about 1 / 3 of the remaining slurry is dropped onto a filter paper equivalent to the three types specified in JIS P 3801 [filter paper (for chemical analysis)] as one sample, and left for 20 seconds to remove excess moisture, and then the mass of the porous cellulose particles remaining on the filter paper is peeled off from the filter paper and weighed to obtain the wet mass of the porous cellulose particles. Next, the porous cellulose particles are dried in an oven at 80°C for 2 hours and then weighed to obtain the dry mass. These operations are carried out for three samples, the ratio of the dry mass to the wet mass is calculated for each sample, and the average of the three values ​​obtained is taken as the solids content.

3. A mixed solution preparation step of preparing a mixed solution by mixing an unsubstituted cellulose solution and a chitosan solution; contacting the mixed solution with a coagulation solvent; Equipped with As a solvent for the mixed solution, an aqueous solution containing an alkali hydroxide and urea is used, The method for producing porous cellulose particles according to claim 1 or 2, wherein the mixed solution preparation step comprises the following steps: A step of dissolving chitosan in an acid-containing aqueous solution, and further mixing an alkali hydroxide and urea to obtain the chitosan solution. A step of mixing unsubstituted cellulose, an alkali hydroxide, urea, and water to obtain a solution of the unsubstituted cellulose. mixing the chitosan solution cooled to a temperature of −10° C. or lower with the unsubstituted cellulose solution;

4. The method for producing porous cellulose particles according to claim 3 , further comprising an acid washing step of washing, with an acid, the porous cellulose particles obtained in the step of contacting the mixed solution with a coagulation solvent.